2020
DOI: 10.1097/md.0000000000018708
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study

Abstract: Sarcopenia is a geriatric syndrome and it impairs physical function. Patients with type 2 diabetes mellitus (T2DM) are at a higher risk of sarcopenia. The purpose of this study is to explore characteristics of general information and metabolic factors of sarcopenia in patients with T2DM in the northeast of China, and provide information for the prevention and treatment of sarcopenia in clinical practice. Patients with T2DM aged ≥65 were recruited in Changchun from March 2017 to February 2018. Quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 37 publications
4
41
0
5
Order By: Relevance
“…In particular, the paper by Cui et al showed that dividing participants according to diabetes duration, the prevalence of sarcopenia was 27.6%, 21.8%, and 52.6%, respectively in the groups with a diabetes duration below 10, between 10 and 20, and above 20 years [ 65 ]. However, other studies [ 49 , 52 , 56 , 57 , 60 , 65 ] did not find any association between disease duration and sarcopenia ( Figure 2 A). This was confirmed by the meta-analysis of Anatagostis et al showing no difference in sarcopenia prevalence between individuals with a mean T2DM duration of ≥9 years or <8.5 years [ 68 ].…”
Section: Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…In particular, the paper by Cui et al showed that dividing participants according to diabetes duration, the prevalence of sarcopenia was 27.6%, 21.8%, and 52.6%, respectively in the groups with a diabetes duration below 10, between 10 and 20, and above 20 years [ 65 ]. However, other studies [ 49 , 52 , 56 , 57 , 60 , 65 ] did not find any association between disease duration and sarcopenia ( Figure 2 A). This was confirmed by the meta-analysis of Anatagostis et al showing no difference in sarcopenia prevalence between individuals with a mean T2DM duration of ≥9 years or <8.5 years [ 68 ].…”
Section: Resultsmentioning
confidence: 72%
“…In some studies, a significantly higher prevalence of sarcopenia in men [ 48 , 63 , 64 ] or women [ 65 , 70 ] was reported. However, other studies [ 47 , 49 , 50 , 51 , 52 , 53 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 66 ] did not find any difference in gender distribution among T2DM with sarcopenia.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations